2018
DOI: 10.1016/j.jse.2018.02.065
|View full text |Cite
|
Sign up to set email alerts
|

Contractile property measurement of the torn supraspinatus muscle using real-time tissue elastography

Abstract: The contractile property of the supraspinatus muscles decreased with an increase in the modified Goutallier stage. Real-time tissue elastography can measure the contractile property of the muscles before surgery and thus may be a predictor for the resulting restoration of lost muscle function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…23,24 Gerber et al and Yuri et al independently demonstrated that the contractility of the torn supraspinatus muscle decreased with increasing fat infiltration. 17,27 These evidences suggest postoperative contractile recovery to be associated with fat infiltration.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…23,24 Gerber et al and Yuri et al independently demonstrated that the contractility of the torn supraspinatus muscle decreased with increasing fat infiltration. 17,27 These evidences suggest postoperative contractile recovery to be associated with fat infiltration.…”
Section: Discussionmentioning
confidence: 97%
“…Many studies have revealed that elasticity decreased with increasing fat infiltration. 17,[23][24][25] Valencia et al demonstrated that interstitial fibrosis advanced with increasing fat infiltration, especially dense collagenous tissue surrounded the marked 26 Theoretically, the collagenous tissue content ratio will be highest in the AR area, modest in the whole area and lowest in the AM-p area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurements were conducted by a single sonographer (KH). Muscle activity was defined as the difference in stiffness values between the resting positions and those during muscle contraction (Δ E = stiffness at contraction − stiffness at rest) [ 20 , 32 , 33 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…The supraspinatus is the most common rotator cuff tendon that is involved in a rotator cuff tear [4][5][6]. Yuri et al demonstrated that the pre-operative contractility of the torn supraspinatus muscle can be measured with real-time tissue elastography (RTE), non-invasively and quantitatively [7]. While functional recovery of the supraspinatus muscle itself is not responsible for entire shoulder functional outcome, it will provide us with important information in the setting of rotator cuff tear and repair.…”
Section: Introductionmentioning
confidence: 99%